Assessment of wind energy potential at Gong Kedak and Pantai Chendering, Malaysia - Chandran, Yutheish; Didane, Djamal Hissein, Mohammed Ogab, Mohammed (FAZ Publishing, 2021)
Nowadays, moving toward renewable energy sources is a crucial step in planning for any country’s economic growth and in determining the viability of any wind development project. Since independence, Malaysia has spent significant resources on increasing its energy capability. As a result, the country’s generation capacity has increased substantially. Wind energy is increasingly being accepted as a significant complementary energy source for securing sustainable and clean energy for the future in Malaysia. However, comprehensive wind energy assessments at some potential sites of the country are still not discovered. Therefore, this stuy is set out to provide assessments of wind energy potentiality at the Gong Kedak in Kelantan and the Pantai Chendering in Terengganu using the 2-parameter Weibull distribution. The recent two years’ period wind speed data of 2019 and 2020 used in this analysis were collected from the wind monitoring station of the Malaysian Meteorological Department. The maximum Weibull parameters (k, c) were 2.64 and 5.21 m/s, and both acted at Pantai Chendering. The Maximum mean wind energy in Pantai Chendering was 7.9 m/s, but the highest at Gong Kedak was only 2.1 m/s over two years period. Gong Kedak recorded 14.68 kWh/m2 in wind energy density, whereas Pantai Chendering recorded 660.29 kWh/m2 . The result presented as a Weibull distribution and analysis indicated that the station at Pantai Chendering has tremendous potential. However, the wind power potential in the site covered in the present study is only adequate for small-scale wind energy applications.